Una aproximación al reformismo político de Rodolfo Rivarola : prácticas, partidos y representación política en un espacio de opinión: "La Revista Argentina de Ciencias Políticas": 1914-1916 - Ferraro, Liliana (2003)
The present historical study on the reflexive analysis of articles writhe by Rodolfo Rivarola in the Argentina Journal of Political Science First published in 1910, the centennial year, over practical, political parties, and political representation (1914 -1916). Contextualialized in the cosmovision of reformist liberal thinking, the journal became an invaluable forum of opinion conveying the idea and values of different political parties, constituting a public cultural political representation of Argentina al the beginning of the 20 Th. Century.